Anemia in inflammatory bowel disease: prevalence, differential diagnosis and association with clinical and laboratory variables - Alves, Rodrigo Andrade (2014)
CONTEXT AND OBJECTIVES: Anemia is the most frequent extraintestinal complication of inflammatory bowel disease. This study aimed to: 1) determine the prevalence of anemia among patients with inflammatory bowel disease; 2) investigate whether routine laboratory markers are useful for diagnosing anemia; and 3) evaluate whether any association exists between anemia and clinical/laboratory variables. DESIGN AND SETTING: Cross-sectional at a federal university. METHODS: 44 outpatients with Crohn’s disease and 55 with ulcerative colitis were evaluated. Clinical variables (disease activity index, location of disease and pharmacological treatment) and laboratory variables (blood count, iron laboratory, vitamin B12 and folic acid) were investigated. RESULTS: Anemia and/or iron laboratory disorders were present in 75% of the patients with Crohn’s disease and in 78.2% with ulcerative colitis. Anemia was observed in 20.5% of the patients with Crohn’s disease and in 23.6% with ulcerative colitis. Iron-deficiency anemia was highly prevalent in patients with Crohn’s disease (69.6%) and ulcerative colitis (76.7%). Anemia of chronic disease in combination with iron deficiency anemia was present in 3% of the patients with Crohn’s disease and in 7% of the patients with ulcerative colitis. There was no association between anemia and disease location. In ulcerative colitis, anemia was associated with the disease activity index. CONCLUSIONS: Most patients present iron laboratory disorders, with or without anemia, mainly due to iron deficiency. The differential diagnosis between the two most prevalent types of anemia was made based on clinical data and routine laboratory tests. In ulcerative colitis, anemia was associated with the disease activity index.